An evaluation of “Family and Friends 3”, an English textbook used for primary school students in Viet Nam: M.A Thesis Linguistics: 60 14 01 11 - Lê, Thị Dung (ĐHNN, 2017)
There is no doubt that materials play an important role in language teaching and learning. However, no textbook is perfect in a particular teaching situation since there is an mixture of components affecting it such as the aims of the course, students‟ interest or students‟ ability. Therefore, materials evaluation is essential in deciding which textbook should be chosen before applying it to any course. This thesis was carried on to evaluate a material which has been in use for primary school students in Vietnam. Although it has been in use for a long time as a popular textbook, there is no research checking whether teachers satisfy with it as well as its appropriateness to the teaching situation in Vietnam in term of both appearance and content.